MiR-124-3p alleviates the dezocine tolerance against pain by regulating TRAF6 in a rat model. Issue 1 (6th January 2021) - Huo, Yan; Zhang, Kun; Zhang, Tao; Han, Yaqi; Hu, Zhenjie
Abstract : MicroRNAs (miRNAs) play important roles in drug tolerance and regulating pain. The purpose of the present study is to explore the regulatory mechanism of miR-124-3p on dezocine tolerance against pain in a rat model. The expression of miR-124-3p and TRAF6 in spinal cord of rats was detected by quantitative reverse-transcription PCR. The paw withdrawal latency (PWL) and maximal potential efficiency % of rats were detected by PWL assay. The levels of IL-1β and TNF-α in spinal cord tissues of rats were measured by ELISA assay. The interaction between TRAF6 and miR-124-3p was predicted by TargetScan software (http://www.targetscan.org ) and confirmed by the dual-luciferase reporter assay. The protein level of TRAF6 was determined by western blot. MiR-124-3p expression was highly downregulated in a dezocine-resistant model. MiR-124-3p overexpression could alleviate dezocine tolerance in rats. TRAF6 expression was significantly upregulated in a dezocine-resistant model. MiR-124-3p targeted TRAF6 and TRAF6 was negatively modulated by miR-124-3p. In addition, overexpression of TRAF6 could reverse the inhibitory effects of miR-124-3p on dezocine tolerance. Overexpression of miR-124-3p alleviates dezocine tolerance against pain via regulating TRAF6 in a rat model, providing a possible solution to address dezocine tolerance in clinical.